Construction of dose response curve for 6 MV LINAC X-rays using Premature Chromosome Condensation assay for radiation dosimetry. (July 2021) - Meenakshi, C.; Venkatachalam, P.; Chandrasekaran, S.; Venkatraman, B.
Abstract: Quantification of chromosomal aberrations in the exposed personnel blood samples is considered as a 'gold standard' and sensitive biomarker in biological dosimetry. Despite technological developments, culture of cells for 48–52 h remains an unmet need in case of triage biodosimetry. Moreover, it is difficult to get sufficient number of metaphase spreads for scoring after high doses of exposures. The technique which causes condensation of chromatin before mitosis using biological or chemical agent is named as Premature Chromosome Condensation (PCC) assay. This assay is considered as an alternative to chromosome aberration assay, particularly at high acute doses of low and high LET radiation. To establish the PCC assay, blood samples were collected from healthy non-smoking individuals (n = 3) and exposed to various doses (0–20 Gy) of 6 MV X-rays at a dose rate of 5.6 Gy/min, using a high energy Linear accelerator (LINAC). Irradiated blood samples were subjected to Calyculin-A induced PCC. About 500 cells or more than 100 Ring Chromosomes (RC) were scored at each dose. Dicentric chromosomes (DC) and acentric fragments were also scored at each dose; the number of chromosomal aberrations in G1, M, G2/M and M/A phase of cell cycle were recorded and the frequency was used to construct the dose response curve. A dose dependent increase in RC and DC frequency were observed with a slope of 0.049 ± 0.002 and 0.30 ± 0.02 respectively. This study is first of its kind to construct a dose response curve for LINAC X-rays using a PCC assay. Highlights: This study is first of its kind to construct dose response curve for LINAC X-rays using PCC assay. Chemically induced PCC is very reliable biodosimetry tool for accidental exposure. PCC rings observed to be appropriate biomarker for high dose exposure. Different types of PCC rings observed in various phases of cell cycle (G2/M, M, M/A) are shown. It is shown that the dicentric chromosomes are suitable only for low dose exposure (<5 Gy).